Paradigma Sosial Profetik dalam Kode Etik Politik di Indonesia - Islamy, Athoillah (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
This study aims to reveal social prophetic values ​​in the principles of political ethics in Indonesia. This research is a qualitative research in the form of literature review. This type of legal research is normative legal research with a philosophical approach. The primary data source of this research is the text of the code of ethics of politicians and political parties. Meanwhile, secondary data sources use various scientific studies that are relevant to the object of discussion. The analytical theory approach used is Kuntowijoyo's social prophetic paradigm theory. This study concludes that the various principles of political ethics in Indonesia are parallel with the values ​​of humanization, liberation and transcendence. First, the principle of public benefit is parallel to the teachings of ukhuwah insaniyah and ta'awun insani. Second, the principle of honesty is parallel to the nature of shiddiq. Third, the principles of integrity and professionalism are parallel to the teachings of the khaira ummah, justice, deliberation, ulul albab, Imamat, and tauhid which are liberating. Fourth, the principle of accountability parallel with amanah. Fifth, this principle of justice is parallel to the universal teaching of Islam in the form of al-adalah.